2020
DOI: 10.18231/2394-2738.2018.0032
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of primary central nervous system tumors in a tertiary hospital, Cairo, Egypt

Abstract: Introduction: In Egypt, few epidemiologic reports have highlighted the national and regional epidemiologic data regarding primary CNS tumors. In this study we aim to identify the frequency of various primary CNS tumors and to demonstrate the age group distribution, gender, topographic data and the different histopathologic types among our patients. Materials and Methods: Data on all cases of primary CNS neoplasms received at Pathology department of Ain Shams University Specialized hospital in addition to a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…In the current study the frequency of meningioma was (13.6%), this finding is lower than results from Hewedi et al (11) and Rigau et al (12) who reported that the frequency of meningioma was (28.8%).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In the current study the frequency of meningioma was (13.6%), this finding is lower than results from Hewedi et al (11) and Rigau et al (12) who reported that the frequency of meningioma was (28.8%).…”
Section: Discussioncontrasting
confidence: 83%
“…This finding comes in agreement with results from Samadi and Ahmadi (15) . However, Hewedi et al (11) revealed predominance of transitional variant (53.1%).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to our findings, a study in Maiduguri, Nigeria showed that intraaxial tumours such as gliomas are more common [ 33 ]. In Abuja Nigeria, a study found that meningiomas were the most common followed by pituitary adenomas and gliomas, similar to reports from India, Egypt, Ghana, England, and USA [ 2 , 8 , 12 , 16 , 26 , 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…In Egypt, gliomas rank first among the primary central nervous system (CNS) tumors, accounting for 35% of all neoplasms. The most common gliomas are astrocytic tumors and glioblastoma represents 44.1% of this category (Hewedi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%